Physicochemical factors affecting mangrove distribution and occurrence in selected sites in the Province of Antique - Agapin, Antonio Dizon Jr. (2009.)
Mangrove forests are unique inter-tidal ecosystems comprised of taxonomically diverse, salt-tolerant tree and other plant species that are primarily found on relatively sheltered coastlines, deltas, estuaries and lagoons in ropical and subtropical regions of the world. The objective of this study is to generally determine the physicochemical factors influencig the distribution and occurence of mangroves in selected sites in the Province of Antique and to specifically measure selected physicochemical factors influencing the distribution and occurence per species per municipality using Pearson Correlation Coefficient.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Mangrove